Acquisition and analysis of aquatic stroke data from an accelerometer based system - Davey, N. P. (2004)
The aim of this work was to develop devices for elite athletes to record performance related parameters during their training. A device was initially designed and built for rowing to record the motion of the boat. This was to gain understanding of motion signals in a one dimensional plane. The device uses a iPAQ handheld computer for recording and display of data to the user.